Women’s Socio-Political Dynamics in Indonesian Literature - Wajiran, Wajiran; Fadillah, Dani (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2020)
Literary works have been believed to be media to spread ideas or ideology. This paper seeks to examine the images of women before Indonesia’s Reformation Era as reflected in Ahmad Tohari's Bekisar Merah and after the Reformation Era as reflected in Ayu Utami's Saman. By employing qualitative modes of inquiry and theories in the sociology of literature, this study has shown that images of women before and after Indonesia’s Reformation Era were depicted differently. Before Indonesia’s Reformation Era, the image of women tended to be submissive in dealing with the socio-political dynamics, while after the Reformation Era in 1998, they were depicted as progressive and even rebellious. However, it is also important to notice that this difference indicated the writers' political and ideological preference in describing the women’s position in Indonesian society in their era. The findings of this study support Gramsci's idea about ideological or cultural hegemony presented by literary work.